2020
DOI: 10.46419/vs.52.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Kemijski sastav i profil masnih kiselina mlijeka alpske i sanske pasmine koza iz Bosne i Hercegovine

Abstract: Interest in the production and sale of goat milk products has been growing over the past 20 years. The chemical composition of goat milk, which greatly affects its nutritional and therapeutic value, makes its products more acceptable to consumers. The aim of this study was to compare the chemical composition and fatty acid profile of Alpine and Saanen goat milk. The results showed that there were differences in certain chemical components between the milk of these two breeds. Protein, fat and ash content in Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Significantly less of C8:0, C10:0, C11:0, C12:0, C14:0, C16:1n7, C17:1n9, C18:2n6t, C18:2n6c,t, C18:2n6t,c, C18:3n3, C20:5n3, C22:4n6, and C22:5n3 whereas more of C4:0, iC14:0, aC15:0, iC17:0, C18:0, C20:0, and C20:1n9 were found in the Saanen compared with the Alpine milk. Vulić et al [ 8 ] also revealed variation of FA in the milk of Alpine and Saanen breeds, however, goats were on different breeding regimes. Earlier studies confirmed FA variation between different goat breeds such as Bulgarian White Dairy Goat and Toggenburg (Pamukova et al [ 35 ]) or Nguni and Boer (Idamokoro et al [ 36 ]) when goats were kept in similar conditions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Significantly less of C8:0, C10:0, C11:0, C12:0, C14:0, C16:1n7, C17:1n9, C18:2n6t, C18:2n6c,t, C18:2n6t,c, C18:3n3, C20:5n3, C22:4n6, and C22:5n3 whereas more of C4:0, iC14:0, aC15:0, iC17:0, C18:0, C20:0, and C20:1n9 were found in the Saanen compared with the Alpine milk. Vulić et al [ 8 ] also revealed variation of FA in the milk of Alpine and Saanen breeds, however, goats were on different breeding regimes. Earlier studies confirmed FA variation between different goat breeds such as Bulgarian White Dairy Goat and Toggenburg (Pamukova et al [ 35 ]) or Nguni and Boer (Idamokoro et al [ 36 ]) when goats were kept in similar conditions.…”
Section: Resultsmentioning
confidence: 99%
“…This study showed that the amounts of LCFA (3.21%) and BCFA (26.14%) was higher in the milk of Saanen goats and lower in MCFA (10.27%) and PUFA (7.52%) compared with Alpine goat milk. Vulić et al [ 8 ] did not reveal variation in SFA and PUFA, although goats being kept under different breeding models, but found a significant difference in the MUFA content between Alpine (22.80 g/100 g) and Saanen (24.00 g/100 g) goats kept in Bosnia and Herzegovina [ 31 ]. According to most studies, the proportion of MUFA in the total FA goat’s milk content can vary from 15 to 30%, and the intrinsic content of oleic acid (C18:1n9c) is the main determining factor (Kuchtik et al [ 10 ]), which coincides with the data of the current study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extracted fat was used for fatty acid methyl esters preparation according to ISO 12966-2 (2015) with some modifications, as described by Vulić et al (2021). Briefly, the extracted fat was dissolved in isooctane, following which a methanolic transesterification was performed.…”
Section: Fatty Acid Methyl Esters (Fame) Analysismentioning
confidence: 99%
“…Šlyžius et al [40] presented results that indicate that the concentration of C8:0 and C10:0 was significantly higher in Alpine goats' milk than in milk obtained from Saanen goats [40]. Moreover, Vulić et al [41], who also examined the milk of Alpine and Saanen goats, also reported the effect of breed on the concentration of caproic acid (C6:0).…”
Section: Fatty Acid Profile Of Bulk Tank Milk Samplesmentioning
confidence: 99%